1990
DOI: 10.1210/endo-126-5-2733
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Committed Mononuclear Precursors for Osteoclast-Like Cells Formed in Long Term Human Marrow Cultures*

Abstract: Nonadherent marrow mononuclear cells enriched for hematopoietic progenitor cells were cultured in semisolid medium with recombinant human granulocyte-macrophage colony-stimulating factor for 9 days to form colony forming unit-granulocyte macrophage (CFU-GM) colonies. 1,25-Dihydroxyvitamin D was then gently layered over the cultures. After 2 weeks, approximately 30% of the colonies that formed were composed of cells with a unique polygonal morphology. One hundred percent of the polygonal cells in these colonies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
118
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(121 citation statements)
references
References 21 publications
3
118
0
Order By: Relevance
“…27 However, CFU-G colonies were increased in CC-4047 cultures at the expense of CFU-GMs. Since CFU-GMderived cells form OCLs at a high efficiency and are recognized as early precursors for OCLs, 37,38 our data indicate that CC-4047 inhibits lineage commitment to CFU-GMs, resulting in impairment of OCL development. The concomitant up-regulation of CFU-G colonies is consistent with our observation that CC-4047 induced the development of high numbers of granulocytic cells.…”
Section: Discussionmentioning
confidence: 75%
“…27 However, CFU-G colonies were increased in CC-4047 cultures at the expense of CFU-GMs. Since CFU-GMderived cells form OCLs at a high efficiency and are recognized as early precursors for OCLs, 37,38 our data indicate that CC-4047 inhibits lineage commitment to CFU-GMs, resulting in impairment of OCL development. The concomitant up-regulation of CFU-G colonies is consistent with our observation that CC-4047 induced the development of high numbers of granulocytic cells.…”
Section: Discussionmentioning
confidence: 75%
“…1, a and b) (17). In addition, the number of osteoclastic cells generated in vitro from whole bone marrow cells of KL ÏȘ/ÏȘ mice was significantly lower than that of wild-type (KL Ï©/Ï© ) mice when osteoclastogenesis was induced with 1,25(OH) 2 vitamin D 3 and PGE 2 (Fig. 1c).…”
Section: Impairment Of Osteoclastogenesis and B Lymphopoiesis Inmentioning
confidence: 91%
“…Osteoclasts, multinucleated cells primarily responsible for bone resorption, have been shown to differentiate from the monocyte/ macrophage lineage (1)(2)(3)(4). Mature osteoclasts can be formed in vitro from bone marrow cells in the presence of two cytokines, M-CSF and osteoclast differentiation factor/receptor activator of…”
mentioning
confidence: 99%
“…Similarly, Hattersley et al"7 reported that IL-3 can stimulate the growth of murine pluripotent stem cells, which in turn can differentiate to calcitonin receptor positive cells that do not resorb bone. Kurihara et al 29 have shown, using human marrow precursor cultures, that IL-3 can increase precursors for osteoclasts, provided that these cells are then sequentially cultured in the presence of 1,25D3. Barton and co-workers"8 have recently reported that IL-3 can also increase multinucleated cell formation in long-term murine marrow cultures.…”
Section: E Interleukin-3mentioning
confidence: 99%